Adding to the Arsenal of Zirconium‐Based Metal–Organic Frameworks: the Topology as a Platform for Solvent‐Assisted Metal Incorporation. Issue 27 (27th September 2016) - Liu, Tian‐Fu; Vermeulen, Nicolaas A.; Howarth, Ashlee J.; Li, Peng; Sarjeant, Amy A.; Hupp, Joseph T.; Farha, Omar K.
Abstract: Invited for the cover of this issue is the group of Omar K. Farha and Joseph T. Hupp from Northwestern University, Evanston, IL, USA. The cover image shows the structure of the zirconium‐based metal–organic framework, NU‐1200, and the principles we use to develop new materials. Abstract : Our method for creating new porous materials follows the instructional sequence of design, construct, and modify… Read more about the story behind the cover in the Cover Profile and about the research itself onp. 4349 ff .